Androgenemia Nervosa - Sanjay Kalra; Madhur Verma; Atul Dhingra; Nitin Kapoor (Journal of the Pakistan Medical Association, 2025)
This brief communication describes androgenemia nervosa, an excessive preoccupation with serum testosterone levels. Commonly noted in young and middleaged men with non-specific symptoms, it may be associated with metabolic disorders such as obesity, stress, substance abuse and other psychiatric disorders. Counselling and support are first-line therapy for this condition. Psychotropic pharmacotherapy is rarely needed. Enhanced public awareness and preventive measures are required to mitigate the effects of androgenemia nervosa. Keywords: Biopsychosocial, hypogonadism, late onset hypogonadism, image disorder, obesity